Retrospective analysis of the clinical efficacy of definitive chemoradiotherapy for patients with hypopharyngeal cancer - Takehana, Keiichi (Jpn J Clin Oncol, 2016)
OBJECTIVE: A retrospective analysis was performed to evaluate the clinical efficacy of definitive chemoradiotherapy including intensity-modulated radiotherapy for patients with hypopharyngeal cancer. METHODS: Previously untreated 204 patients with hypopharyngeal cancer were treated with definitive chemoradiotherapy. Of note, 66–70 Gy was delivered to the primary and involved nodes and 36–54 Gy was delivered to the prophylactic lymph node using standard fractionated radiotherapy. One hundred and forty-six patients received induction chemotherapy as a larynx preservation strategy, followed by definitive radiotherapy with or without concurrent chemotherapy. Intensity-modulated radiotherapy was also performed after 2006. RESULTS: The median follow-up time of this cohort was 43.4 months (range; 6.9–151.0). The 3-year overall survival, progression-free survival and larynx preservation survival rates were 78.8% (95% confidence interval; 73.0–85.0), 58.4% (95% confidence interval; 51.8–65.9) and 67.5% (95% confidence interval; 61.0–74.7), respectively. Multivariate analyses identified the following significant prognostic factors: an advanced age, the T category and N category for overall survival, the T category and N category for progression-free survival and the T category for larynx preservation survival. Acute toxicities of Grade 3 or higher were observed in 47 patients (23.0%). Two patients (1.0%) had Grade 4 pharyngeal edema. Suspicious treatment-related death due to lethal pharyngeal hemorrhage occurred in 1 (0.4%) patient. The rates of Grade 2 xerostomia in patients treated with intensity-modulated radiotherapy were 28.1, 17.4 and 9.5% at 6 months, 1 and 2 years after the completion of radiotherapy, respectively. CONCLUSIONS: The efficacy and safety of definitive chemoradiotherapy are considered feasible with sufficient laryngeal preservation.